2014
DOI: 10.1021/ma500451g
|View full text |Cite
|
Sign up to set email alerts
|

Wall Slip of Bidisperse Linear Polymer Melts

Abstract: We have characterized the effect of molecular weight distribution on slip of linear 1,4-polybutadiene samples sandwiched between cover glass and silicon wafer. Monodisperse polybutadiene samples with molecular weights in the range of 4–195 kg/mol and their binary mixtures were examined at steady state in planar Couette flow using tracer particle velocimetry. Slip velocity was measured at shear rates over the range of ∼0.1–15 s–1. Our results revealed that weakly entangled short chains play a crucial role in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 46 publications
(93 reference statements)
2
48
0
Order By: Relevance
“…Phenomena that occur in the flow field of polymer melts, such as flow rate discontinuity (spurt) and oscillatory flow, show the important role of the weak slip and the strong slip in the flow dynamics of polymers . In polymer processing, wall slip generally has a beneficial effect by releasing the shear stress at the wall and reducing the required pressure for a certain flow rate . Nevertheless, the wall slip behavior of polymers in various practical processing methods still remains ambiguous because of the large number of influential factors and the complexity of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Phenomena that occur in the flow field of polymer melts, such as flow rate discontinuity (spurt) and oscillatory flow, show the important role of the weak slip and the strong slip in the flow dynamics of polymers . In polymer processing, wall slip generally has a beneficial effect by releasing the shear stress at the wall and reducing the required pressure for a certain flow rate . Nevertheless, the wall slip behavior of polymers in various practical processing methods still remains ambiguous because of the large number of influential factors and the complexity of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, wall slip has been speculated as a potential cause for such anomalous behavior as ultra‐strain softening associated with stress relaxation from large‐magnitude stepwise shear . More recently, many visualization‐based studies have been made to demonstrate polymer wall slip . These studies do not present any challenge to the existing knowledge because the prevailing theoretical paradigm for bulk rheology, based on the tube model, does not deal with the experimental reality of wall slip.…”
Section: Introductionmentioning
confidence: 99%
“…[16] More recently, many visualization-based studies have been made to demonstrate polymer wall slip. [11,[17][18][19][20][21][22][23][24][25] These studies do nonlinear rheology of entangled polymers, that is, the tube theory. [27,30] This paper is confined to a) review the pertinent literature surrounding the phenomena of shear strain localization in entangled polymer solutions and melts, b) indicate the successful description of wall slip, and c) discuss the remaining challenges.…”
Section: Introductionmentioning
confidence: 99%
“…For HDPE‐B resin which has broader MWD and more low MW polymer, the steady shear stresses before slip‐stick transition were slightly lower than the complex modulus magnitude possibly due to small degree of wall slip. It was recently reported that small chains could be concentrated near the wall by flow‐induced fractionation and result in wall slip . The slip‐stick transitions reached at critical stresses of 342 and 275 kPa for HDPE‐A and HDPE‐B, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…They postulated that a step discontinuity in the velocity profile arises within the polymer stream in addition to the wall slip, so that the cohesive slip layer then emerges from the die exit and collects onto the open face of the extrusion die. It was suggested that the cohesive slip theory is not to be confused with the hypothesis of a “low viscosity layer at the die wall” that arises when a low molecular weight polymer fractionates and then migrates toward the die wall . Whereas cohesive slip involves a step discontinuity in the velocity profile within the polymer, the hypothesis of a “low viscosity layer at the die wall” occurs over a very small relevant neighborhood of the wall.…”
Section: Discussionmentioning
confidence: 99%